High-Speed Rail Diplomacy as Connectivity for the Belt and Road Initiative and its Potential Implication for Thailand - KHONKHLONG, SUPPAKORN (Thai Journal of East Asian Studies, 2022)
The Chinese government believes that high-speed rail construction can benefit Belt and Road country transportation and regional economies. The creation of a high-speed rail system immediately benefits these national capabilities, and transportation planning contributes to economic development and helps close regional development gaps. Therefore, this article examines a case study of Chinese high-speed rail development history, current status, and impact on the regional economy. In addition, opportunities and risks of constructing a Sino-Thai high-speed rail are considered by analyzing the successful example of the Beijing-Shanghai high-speed rail, and management and policy recommendations are offered for high-speed rail construction and operation in Thailand.